2022
DOI: 10.1111/jocs.16425
|View full text |Cite
|
Sign up to set email alerts
|

Total arterial coronary artery bypass grafting in patients with preoperative anemia

Abstract: Objectives Blood transfusions after coronary artery bypass grafting (CABG) has been associated to adverse outcomes, especially in anemic patients. However, little is known about the influence of the modality of revascularization. Total arterial revascularization (TAR) was shown to reduce postoperative transfusion when compared to saphenous vein‐based (SV)‐CABG (LIMA plus one/more SV grafts). We, therefore, aimed to investigate the impact of TAR‐CABG versus SV‐CABG on blood products use and perioperative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that preoperative anemia can increase morbidity and mortality, prolong ICU and hospital stay times in adult cardiac surgery [ 13 , 14 ]. The pathophysiology basis of anemia is the reduction of oxygen-carrying capacity for Hb, which can result in tissue hypoxia and organ dysfunction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that preoperative anemia can increase morbidity and mortality, prolong ICU and hospital stay times in adult cardiac surgery [ 13 , 14 ]. The pathophysiology basis of anemia is the reduction of oxygen-carrying capacity for Hb, which can result in tissue hypoxia and organ dysfunction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%